Valoração contigente de um projeto de recuperação de qualidade das águas - o caso do córrego Limoeiro em Presidente Prudente, SP - Pontes, Márcio Rogério (2009)
The purpose of this work is to evaluate, according to the population s perception, the benefit to the environment by treating the sanitary sewers flowing into the Limoeiro stream located in Presidente Prudente, in the state of Sao Paulo. It is sometimes difficult to place a value on natural resources and this research attempts to develop a method to place a value to this particular natural resources, the Limoeiro stream. By making it possible to have a base of common comparison, the financial value, provides a justification for investments in environment conservation projects. With this objective, the contingent valuation method was used to evaluate the natural resource which investigated the disposition of the population to pay for this process in two types of scenarios. In the first scenario, which presents the legal view of the conservation, determined that it would be R$ 5,12 with 95% of entrust and a plus or minus 10% margin of error. In the second scenario, which presents the ideal view of the water course conservation would be R$ 7,35 also showing a 95% entrust and a plus or minus 10% margin of error. A period of 30 years was stipulated and the global liquid present value between R$ 9.126.914,16 to R$ 16.011.288,26 with a discount tax of 12% of the capital.